2010
DOI: 10.1080/09602011.2010.509190
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Cerebral Palsy Quality of Life for Children (CP QOL-Child) questionnaire for use in Chinese populations

Abstract: The purpose of this study was to examine the psychometric properties of the Chinese version of Cerebral Palsy Quality of Life for Children (CP QOL-Child) questionnaire. We performed forward (into Chinese) and backward translation of the CP QOL-Child for: (1) the primary caregiver form (for parents of children with CP aged 4-12 years); and (2) the child self-report form (for children with cerebral palsy aged 9-12 years). Psychometric properties assessed included test-retest reliability, internal consistency, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 25 publications
6
32
1
Order By: Relevance
“…The reliability and validity of C CP QOL-Child has been assessed using CTT. 18 The current study further validated and refined the instrument using item response theory (IRT), more specifically the Rasch model. a Gross motor function classification system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reliability and validity of C CP QOL-Child has been assessed using CTT. 18 The current study further validated and refined the instrument using item response theory (IRT), more specifically the Rasch model. a Gross motor function classification system.…”
Section: Discussionmentioning
confidence: 99%
“…When using the CTT approach, 18 results of the principal components analysis followed by varimax rotation showed that the 62-item scale (in the Wang et al study, three items in the domain access to services had been excluded from the principal component analysis as many participants did not provide a response) cumulatively accounted for 57.7% of the variance. In this study using the IRT approach, results of the residual analysis for the original 65-item scale showed that the cumulative variance explained was 56.4%.…”
Section: Ctt Versus Irt (Reliability and Validity)mentioning
confidence: 97%
See 2 more Smart Citations
“…There were no significant differences between groups found postintervention (8wks after baseline) for children's (Table II). Children in both groups scored in the normal range on the Strengths and Difficulties Questionnaire, 27 Child and Adolescent Mindfulness Measure, 26,43 the parent-reported CP QOL-Child, 44,45 and the Behaviour Rating Inventory of Executive Function 25 at baseline, and hence this may reflect a ceiling effect.…”
Section: Children's Psychological Well-beingmentioning
confidence: 99%